2008
DOI: 10.1177/0003319708325449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weight Reduction with Dietary Intervention on Arterial Distensibility and Endothelial Function in Obese Men

Abstract: Obesity and reduction in central arterial distensibility, respectively, have been identified as powerful and independent risk factors for cardiovascular disease. However, the effect of weight reduction on central arterial function in obese subjects has not yet been clarified. We investigated whether low-calorie diet-induced weight reduction affects central arterial distensibility and endothelial function in middle-aged obese men. Twelve obese men (age: 45+2 yrs, BMI: 30+1 kg/m 2) completed a 12-week dietary in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 28 publications
(38 reference statements)
7
48
0
1
Order By: Relevance
“…The present study confirms previous observations reporting increased PWV with aging, 22,26 high BP, 14,22,26 and obesity 33 in the entire study population. No relation was found between PWV and cholesterol in our study and was in keeping with some previous studies 34,35 but not all.…”
Section: Arterial Stiffness and CV Variables In The Whole Studysupporting
confidence: 92%
“…The present study confirms previous observations reporting increased PWV with aging, 22,26 high BP, 14,22,26 and obesity 33 in the entire study population. No relation was found between PWV and cholesterol in our study and was in keeping with some previous studies 34,35 but not all.…”
Section: Arterial Stiffness and CV Variables In The Whole Studysupporting
confidence: 92%
“…Briefly, the dietary modification protocol is a low-calorie diet intervention that affects body composition, body fat distribution, and coronary heart disease risk factors [16,17]. Based on the diet protocol used in this study, all of the participants were instructed to take meals consisting of an average of 420 kcal of protein, 840 kcal of carbohydrate, and 420 kcal of fat per day (1680 kcal/day).…”
Section: Lifestyle Modificationmentioning
confidence: 99%
“…The present study adds to a number of investigations, which have consistently shown a reduction in cfPWV over the short term, following different lifestyle interventions, including not only physical exercise [11][12][13][14][15][16] but also weight loss, smoking cessation and salt intake restriction [17][18][19][20][21][22][23][24][25] (Table 1).…”
mentioning
confidence: 58%